EFEKTIVITAS SEKOLAH RAMAH ANAK DALAM MEMBANGUN KARAKTER SPIRITUAL SISWA DI ERA DIGITAL - Suryani, Heni; Akhmad Affandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine how effective child-friendly schools are in building students’ spiritual character in the era of computers and the internet. This study used a literature study, which focused on collecting and analyzing literature relevant to the topic discussed. This study aims to gain a deep understanding of the practices that have been carried out and the problems faced in today’s education world. The results of this study found many educational approaches used in Child-Friendly Schools. These strategies include incorporating spiritual values into the curriculum, incorporating relevant extracurricular activities, and using pedagogical approaches that encourage active student participation. The findings indicate that with the right approach, child-friendly schools can function as an effective environment in building students’ spiritual character so that they are not only able to compete academically but also have integrity and a positive attitude in interacting in the digital era.